Identifikasi Miskonsepsi Terhadap Konsep Larutan Penyangga Dengan Menggunakan Instrumen Tes Diagnostic Four-Tier Multiple Choice - Muthiah Afifah, Intan; Irwandi, Dedi; Murniati, Dewi (LPPM Universitas Negeri Jakarta, 2021)
Student misconception is one of the important concerns in educational research because it is disturbing students to understand the scientific concepts in learning. Misconceptions often occur in Chemistry learning, one of them on the concept of Buffer Solution. This study aims to identify students' misconception on the concept of Buffer Solution using Four-Tier Multiple-Choice (4TMC) test instrument in SMA Negeri South of Tangerang. The research method used is descriptive quantitative. The study was conducted on 07 August to 05 September 2019. The subjects of this study are the students of XII grade MIPA program in SMA Negeri South of Tangerang academic year 2019/2020 with the number of samples 134 students taken from four classes using the technique of Cluster Random Sampling. The research data was obtained from the students' answers on the 4TMC test questions. The data is processed based on the pattern of student answers are then grouped into the category of student understanding that is misconception, lack of knowledge, error, and understand the concept. The results showed that there was a misconception with a percentage (48,51%), and significant misconceptions identified in 2 of 5 subconcepts of Buffer Solution investigated, they are the subconcept of Buffer Solution Calculation (14.92%), The Role Of Buffer Solutions In The Body Of Living Things (15.67%). The result of the identification of student misconception is expected to identify misconceptions that occur in the students to be handled more quickly so as not to impede the students in learning. Keywords: Misconception, Buffer Solution, Four-Tier Multiple-Choice Test